PHYTOCHEMICAL AND ANTIOXIDANT ACTIVITY TESTS OF RAMBAI WOOD EXTRACT (Baccaurea motlyeana Mull.Arg.) - Manik, Rike Dominta Aprianti; Erwin, Erwin; Alimuddin, Alimuddin (JURNAL ATOMIK, 2019)
Phytochemical and antioxidant activity tests of crude extract and their fractions on stem of rambai (Baccaurea motleyana Mull.Arg.) were carried out. This research was conducted to determine the antioxidant properties of crude extract, n-hexane fraction, ethyl acetate fraction, and methanol fraction. The phytochemical test was carried out by a color test while the antioxidant activity test was carried out by the DPPH method. Phytochemical test result showed crude extracts containing alkaloids, steroids, flavonoids and phenolic compounds. The n-hexane fraction contains a group of alkaloids and steroids. Ethyl acetate fraction contains steroid, flavonoid and phenolic compounds. The remaining methanol fraction contains triterpenoid and phenolic compounds. Antioxidant activity test result showed that the crude extract, n-hexane fraction, ethyl acetate fraction and the remaining methanol fraction had IC50 values ​​of 127.1032; 58.2275; 32.3562 and 56.4567 ppm, respectively. Based on the result of the antioxidant test, the stem of rambai (Baccaurea motleyana Mull.Arg.) is a plant that has the potential as an antioxidant.